Prostate Cancer Bone Metastasis: Molecular Mechanisms of Tumor and Bone Microenvironment - Jiang H (Cancer Management and Research)
Hua Jiang Department of Urology, Fifth Affiliated Hospital of Zunyi Medical University (Zhuhai Sixth People’s Hospital), Zhuhai, People’s Republic of ChinaCorrespondence: Hua Jiang, The Fifth Affiliated Hospital of Zunyi Medical University (Zhuhai Sixth People’s Hospital), No. 1439, Zhufeng Road, Zhuhai, 519100, People’s Republic of China, Tel +8613726205880, Email jianghua426@zmu.edu.cnAbstract: Prostate cancer is prevalent among men aged 65 and older. Bone metastasis occurs in up to 90% of advanced prostate cancer patients, metastatic prostate cancer is generally considered a non-curative condition which can impact quality of life. The tumor microenvironment, comprising diverse cellular and non-cellular elements, interacts with prostate cancer cells to affect tumor growth and bone metastasis. Within the bone microenvironment, different cell types, including osteoblasts, osteoclasts, adipocytes, endothelial cells, hematopoietic stem cells, and immune cells, engage with tumor cells. Some cells alter tumor behavior, while others are impacted or overpowered by tumor cells, leading to different phases of tumor cell movement, dormancy, latency, resistance to treatment, and advancement to visible bone metastasis. This review summarizes recent research on the tumor microenvironment and bone microenvironment in prostate cancer bone metastasis, exploring underlying mechanisms and the potential value of targeting these environments for treatment.Keywords: prostate cancer, tumor microenvironment, bone microenvironment, epithelial-mesenchymal transition, bone metastasis, tumor dormancy